Erlec1 controls bone metabolism by affecting osteoblast type I collagen synthesis - Chunbao Rao; Wenbo Cui; Zitian Lin; Yaozhong Zhang; Wei Lai; Qi Peng; Xiaomei Lu (Translational Medicine of Aging)
Erlec1 gene has been suggested to be involved in the regulation of bone development. However, the underlying mechanism remains largely unknown. In this study, we showed that loss of Erlec1 leads to growth retardation in mice. Erlec1−/− mice exhibited increased proliferation, delayed differentiation and mineralization in osteoblasts accompanied by decreased production of collagen I. Our data demonstrated that Erlec1 regulates bone formation through modulating proliferation and differentiation of osteoblasts by affecting the synthesis of collagen I, suggesting that Erlec1 may serve as a potent target for bone metabolism diseases.